DETERMINANTS OF DRINKING BEHAVIOR IN KIDNEY STONE DISEASE - Khalifatus Zuhriyah Alfianti; Nurul Imam; Ni Putu Diah Ayu Rusmeni; Nurul Fahmi Rizka Laily; Welmince Paulina Nggorong (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2025)
Introduction: Kidney stones (nephrolithiasis) are a common condition that can reduce the quality of life of those affected. One of the main factors influencing the formation of nephrolithiasis is poor hydration, which can lead to higher concentrations of stone-forming substances in the urine. Poor hydration habits, such as not drinking enough water, can increase the risk of nephrolithiasis. Method: This study is a quantitative study using the case-control method with a retrospective approach. The sample consisted of 32 respondents selected through purposive sampling. Result: This study found that drinking patterns affect the incidence of kidney stone disease (OR = 4.000) with a confidence level (IK) of 95% (1.712 - 9.346). Conclusion: From these results, it can be concluded that respondents with risky drinking patterns have a 4,000 times greater chance of developing kidney stones than respondents who do not have kidney stones. Keywords: determinants, drinking habits, kidney stones